Biogas Production from Local Biomass Feedstock in the Mekong Delta and Its Utilization for a Direct Internal Reforming Solid Oxide Fuel Cell - Shiratori, Yusuke; Yamakawa, Takeo; Sakamoto, Mio; Yoshida, Hinomi; Kitaoka, Takuya; Tran, Quang Tuyen; Doan, Duc Chanh Tin; Dang, Mau Chien (Frontiers in Environmental Science, 2017)
Fuel-flexible solid oxide fuel cell (SOFC) technologies are presently under study in a Vietnam-Japan international joint research project. The purpose of this project is to develop and demonstrate an SOFC-incorporated energy circulation system for the sustainable development of the Mekong Delta region. Lab-scale methane fermentation experiments in this study with a mixture of biomass feedstock collected in the Mekong Delta (shrimp pond sludge, bagasse, and molasses from sugar production) recorded biogas production yield over 400 L kgVS−1 with H2S concentration below 50 ppm level. This real biogas was directly supplied to an SOFC without any fuel processing such as desulfurization, methane enrichment and pre-reforming, and stable power generation was achieved by applying paper-structured catalyst (PSC) technology.